Peran Dukungan Organisasi Yang Dirasakan Karyawan Sebagai Mediator Pengaruh Keadilan Prosedural Terhadap Perilaku Kewarganegaraan Organisasi - - Fatdina (Jurnal Psikologi, 2009)
This study was aimed to identify the influence of procedural justice toward organizational citizenship behavior through perceived organizational support as mediator. The hypothesis posed in this study were procedural justice positively influenced perceived organizational support and procedural justice positively influenced organizational citizenship behavior through perceived organizational support as mediator. This study used random sampling. The subjects of this study were 96 nurses of Dr. Soeradji Tirtonegoro hospital in Klaten, Central Java. Data were collected based on three scales, i.e. procedural justice, perceived organizational support, and organizational citizenship behavior scales. Structural equation model was used to analyze data. The results indicated that procedural justice had very significant and positive effect on perceived organizational support (direct effects = 0,44), whereas procedural justice had negative effect on organizational citizenship behavior through perceived organizational support as mediator (indirect effect = ‐0,11).